A novel non-targeted screening method for urinary exposure biomarker discovery of phthalates using liquid chromatography-mass spectrometry. Issue 9 (15th February 2018) - Yao, Chunhe; Wang, Jianhua; Chan, Peter; Feng, Yong-Lai
Abstract : Phthalates are a group of compounds widely used in consumer products and they are ubiquitous in the environment due to their widespread commercial use. Abstract : Phthalates are a group of compounds widely used in consumer products and they are ubiquitous in the environment due to their widespread commercial use. In this study, a new non-targeted screening method has been developed to identify phthalate metabolites in human urine samples as exposure markers of phthalates using mass spectrometry. The method firstly scanned precursor ions that contained the deprotonated benzoate ion, [C6 H5 COO] −, at m / z 121 using liquid chromatography-tandem mass spectrometry (LC-MS/MS), which is specifically a common fragmentation ion of all phthalate metabolites. The daughter ions of the precursor ions were subsequently scanned using high-resolution mass spectrometry (HRMS) to elucidate their potential structures using accurate mass and fragmentation patterns. Agilent MassHunter software was used to calculate the potential formulas based on the accurate masses of unknown metabolites, and SciFinder was used to narrow down the targets. The fragmentation patterns of phthalate monoesters in mass spectrometry have been investigated for application in the identification of new metabolites in this study. The method has been validated with commercially available standards of phthalate metabolites and applied to identify phthalate metabolites in human urine samples. Nine known phthalate metabolites and an unknown phthalate metabolite have been identified in urine samples. The structure of the new metabolite was proposed as 1, 2-benzenedicarboxylic acid, mono(9-cyclopropylnonyl) ester. This study has demonstrated that the non-targeted method developed could be a useful tool in exposure biomarker discovery.